2020
DOI: 10.15171/jlms.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Polarized Low-Level Laser in the Treatment of Patients With Myofascial Trigger Points in the Trapezius Muscles

Abstract: Introduction: This study assessed the effect of polarized low-level laser therapy (PLLLT) on the treatment of myofascial trigger points (MTrPs) in the trapezius muscles. Its effectiveness in pain reduction was compared to low-level laser therapy (LLLT). Methods: Sixty-four patients with MTrPs were randomly divided into 2 groups, namely PLLLT and LLLT. Each patient received treatment for a period of 2 weeks, 5 sessions a week. The intensity of laser irradiation to the skin surface was 6 J/cm 2 . The system exit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…They found that both techniques effectively treat MTrPs and reduce pain, limitation of neck movement, and PPT. However, the effect of the LLLT was more significant in comparison to the PLLLT (52). Waseem et al (2020) in their study found that the combination of conventional physical therapy and LLLT was more effective than conventional physical therapy alone on PPT and CROM in patients with a trigger point in their UT muscle (53).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They found that both techniques effectively treat MTrPs and reduce pain, limitation of neck movement, and PPT. However, the effect of the LLLT was more significant in comparison to the PLLLT (52). Waseem et al (2020) in their study found that the combination of conventional physical therapy and LLLT was more effective than conventional physical therapy alone on PPT and CROM in patients with a trigger point in their UT muscle (53).…”
Section: Discussionmentioning
confidence: 93%
“…Results of some of the previous research are in line with those of this study in terms of the efficacy of LLLT on the decrease of symptoms of MTrPs. Shahimoridi et al (2020) compared the effects of LLLT and polarized low-level laser therapy (PLLT) on the treatment of MTrPs in the trapezius muscle. They found that both techniques effectively treat MTrPs and reduce pain, limitation of neck movement, and PPT.…”
Section: Discussionmentioning
confidence: 99%
“…The application of LED to the masticatory muscles affects the local tissues around the light application site and previous studies have shown the effectiveness of LED treatment in muscle tissues [ 26 , 27 , 28 ]. The literature also reports that it is possible to observe systemic responses through light therapy, with the action of deep light stimulation directly on the brain [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our results, other similar treatments were effective in reducing mechanical hyperalgesia compared to control groups. The main difference was that the technique was applied on active MTPs rather than on latent MTPs [50]. Despite this clinical difference, an increase in generalized hyperalgesia pressure can be found in asymptomatic participants with latent MTPs [51], and their treatment may reduce latent MTP hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%